2022
DOI: 10.1002/smll.202203554
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization of Antimonene and Bismuthene Nanosheets

Abstract: Antimonene and bismuthene are promising members of the 2D pnictogen family with their tunable band gaps, high electronic conductivity, and ambient stability, making them suitable for electronic and optoelectronic applications. However, semi‐metal to semiconductor transition occurs only in the mono/bilayer regime, limiting their applications. Covalent functionalization is a versatile method for tuning materials’ chemical, electronic, and optical properties and can be explored for tuning the properties of pnicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
(88 reference statements)
1
13
0
2
Order By: Relevance
“…Rao et al also covalently functionalized antimonene and bismuthine nanosheets using p -nitrobenzene diazonium salts. 183 The study of the reaction mechanisms demonstrated the transfer of lone pairs of electrons from the metallic Sb to the diazonium salts, forming a quaternary Sb+ species with organic moieties predominantly attached through Sb–C bonds. This functionalization led to lattice distorsion and charge transfer in the antimonene nanosheets, reducing their bandgap from 2.23 to 2.18 eV, demonstrating the tunability of the optical properties and surface passivation.…”
Section: Novel Insights On the Characterization And Chemical Reactivi...mentioning
confidence: 99%
“…Rao et al also covalently functionalized antimonene and bismuthine nanosheets using p -nitrobenzene diazonium salts. 183 The study of the reaction mechanisms demonstrated the transfer of lone pairs of electrons from the metallic Sb to the diazonium salts, forming a quaternary Sb+ species with organic moieties predominantly attached through Sb–C bonds. This functionalization led to lattice distorsion and charge transfer in the antimonene nanosheets, reducing their bandgap from 2.23 to 2.18 eV, demonstrating the tunability of the optical properties and surface passivation.…”
Section: Novel Insights On the Characterization And Chemical Reactivi...mentioning
confidence: 99%
“…[82,83] In addition to the Bi materials mentioned above, bismuthene (2D bismuth, 2D-Bi) is a promising material for use in energy storage and catalysis due to its tunable bandgap and high conductivity. [86,87] 2D-Bi is known to exhibit a high charge carrier mobility due to its 0.99 eV bandgap which, combined with its high air stability, means that it has a wide range of electronic and energy applications. [88,89] 2D-Bi is known to have three phases (α-, β-, and ξ-), but only the first two have been experimentally obtained and reported to have theoretical stability.…”
Section: Bismuth: Classification and Propertiesmentioning
confidence: 99%
“…The mechanism of covalent functionalization of bismuthene is also proposed to expand the ways of property modulation of bismuthene. 28 Altering the surface structure by anchoring or doping singleatom impurities is critical to obtain practical 2D-material based gas detectors. In this study, we investigated the detection performance of buckled honeycomb-like single atom modified two-dimensional bismuthene for the toxic gas H 2 S. We also compared the effects of different single-atom introduction methods (anchoring and doping) on the geometrical structure, electronic structure and gas sensing ability of bBi.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of covalent functionalization of bismuthene is also proposed to expand the ways of property modulation of bismuthene. 28…”
Section: Introductionmentioning
confidence: 99%